1969
DOI: 10.1099/00221287-56-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Spores of Clostridium botulinum Strain 33 A in Irradiated Ground Beef

Abstract: (4-5 Mrad.) do not completely inactivate spore toxin or enzymes. The present study concerns spore toxin during and after irradiation of 4 x I O~ spores of Clostridium botulinum per g. of canned ground beef irradiated to 4-5 Mrad., at temperatures of -25", 0" and +25". During subsequent incubation of irradiated samples at 30" for 10 months, periodic analyses showed no viable spores. Toxin was tested on (i) non-homogenized samples and (ii) samples homogenized in a tissue grinder.In samples irradiated at -25" and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This might be the reason that the aforementioned studies have reported the presence of BoNT in gamma-sterilized food [ 91 , 91 , 107 , 108 , 109 ]. Fernandez et al [ 110 ] studied the toxicity of strain 33A spores in canned ground beef irradiated to 45 kGy at temperatures of −25, 0, and 25 °C; they found small minimal lethal doses of toxin in the irradiated samples which could be due to (i) the germination of irradiated spores, (ii) slow lysis of spores at 25°, (iii) new toxin synthesis by those spore enzymes which remained active after irradiation, (iv) activation or fragmentation of pre-existing toxin molecules, etc. Meanwhile, the irradiation in combination with high temperatures (i.e., >40 °C) can synergistically inactivate the BoNT [ 17 ].…”
Section: Ionizing Radiations To Inactivate C Botulinummentioning
confidence: 99%
“…This might be the reason that the aforementioned studies have reported the presence of BoNT in gamma-sterilized food [ 91 , 91 , 107 , 108 , 109 ]. Fernandez et al [ 110 ] studied the toxicity of strain 33A spores in canned ground beef irradiated to 45 kGy at temperatures of −25, 0, and 25 °C; they found small minimal lethal doses of toxin in the irradiated samples which could be due to (i) the germination of irradiated spores, (ii) slow lysis of spores at 25°, (iii) new toxin synthesis by those spore enzymes which remained active after irradiation, (iv) activation or fragmentation of pre-existing toxin molecules, etc. Meanwhile, the irradiation in combination with high temperatures (i.e., >40 °C) can synergistically inactivate the BoNT [ 17 ].…”
Section: Ionizing Radiations To Inactivate C Botulinummentioning
confidence: 99%